Global warming and fluvial geomorphology - Goudie, Andrew S. (Geomorphology, 2006)
Keywords: Ouvrage_Collectif_Numéro1

Race, class, and Hurricane Katrina: Social differences in human responses to disaster. - Elliott, James R.; Pais, Jeremy (Social Science Research, 2006)
Hurricane Katrina pounded the Gulf South at the end of August 2005, devastating lives and raising questions about how race and class influence human, as well as institutional, responses to disaster. This study uses survey data collected from over 1200 Hurricane Katrina survivors to examine these influences on a wide array of responses, ranging from evacuation timing and emotional support to housing and employment situations and plans to return to pre-storm communities. Results reveal strong racial and class differences, indicating that neither of these dimensions can be reduced to the other when seeking to understand responses by survivors themselves. This intersection renders low-income black home owners from New Orleans those most in need of targeted assistance as residents work to put themselves and the region back together.